Method construction of front entry porch for the project of Hotel Lanai Casuarina, Kuala Kangsar, Perak - Ahmad Rizal, Ahmad Syafiq (Universiti Teknologi MARA, Perak, 2019)
The study briefly explained regarding the method of construction and the planning of main entrance porch for Hotel Lanai Casuarina located at Kuala Kangsar, Perak. This result obtained through the achievement of three objectives such as to determine the planning that need to take consideration before constructing porch at hotel main entrance, to investigate the method construction of the main entrance porch as well as to determine the problem and solution during constructing the main entrance porch. Through planning aspect, there are four (4) main items must be considered; manpower, material, machinery and money. On the other hand, the method constructing porch at the main entrance revealed there were six steps which were excavating top soil, assembly the timber formworks of pad footing, ground beam, column and roof beam, fabricating the reinforcement bars, concreting work, dismantled the timber formworks, roofing including finished work process.